Social Exclusion in Ancient Egypt: A Sociological Approach - Jiménez Meroño, Beatriz (Cambridge Archaeological Journal, 2023)
Social exclusion has been faced in modern societies as a phenomenon to be prevented in terms of equality. However, it can also be explored in past societies, where some individuals could confront situations of marginalization and exclusion. Previous scholars have accepted or rejected the existence of social exclusion in Ancient Egypt, although none of them has employed a theoretical framework to study it. This paper shows social exclusion as a phenomenon present in Ancient Egypt, analyses the available Egyptian evidence from a theoretical basis inherent to the social sciences, especially Sociology, and applies it to two case studies.
Keywords: social exclusion; ancient Egypt; Scopus